Cog graft, a new septal extension graft for designing nasal tip rotation and projection in rhinoplasty - Soylu, Erkan; Yenigün, Alper; Özturan, Orhan (W.B. Saunders, 2024)
Background: Adjusting the nasal tip rotation and tip projection according to the patient's face and wishes is a very important stage in rhinoplasty with the use of a cog graft positioning the tip point in the appropriate place is possible by adjusting the nose length, tip projection and tip rotation together. Objective: The aim of this study is to facilitate positioning the tip rotation and projection in the appropriate place according to the patient's needs in rhinoplasty with Cog graft. Materials and methods: Cog graft was applied in 32 patients who underwent rhinoplasty. Cog graft was prepared from costal cartilage in 10 patients and from septal cartilage in 22 patients. Cog graft was prepared by shaping the superior edge of the septal extension graft like a gear wheel. It is fixed to provide desired projection to the caudal septum. In the position where rotation and projection are evaluated adequately, the graft is fixed with sutures. They were followed in average 18 months (between 6 and 24 months). Results: Twenty of the patients were primary cases and 12 were revision cases. The targeted rotation and projection results were achieved in all patients. All patients had satisfactory esthetic results. Conclusions: Cog graft is a useful graft with which we can adjust the nose length, projection and rotation appropriately and in a short time with a single graft.
Keywords: Cog Graft; Projection; Rhinoplasty; Rotation; Septal Extension Graft